I always carry my bones - Zamora, Felicia M. (Iowa poetry prize., 2021)
"Home is a complex ideation for many POC and migrant peoples. I Always Carry My Bones explores how familial history echoes inside a person and the ghosts of lineage dwell in a body. Sometimes we haunt. Sometimes we are the haunted. Pierced by an estranged relationship to Mexican culture, the ethereal ache of an unknown father, the weight of racism and poverty in this country, the indentations of abuse, and a mind/physicality affected by doubt, these poems root in the search for belonging-a belonging inside and outside the flesh. Space-making requires a clawing at the atrocities of today's social injustices. Space-making requires a dismantling of violent systems against brown and black bodies. Home is the place where the horrid and beautiful intertwine and carve a being into existence. At times, the reaction is recoil: "biomimicry-how I adapt away/ from you-biomimicry-as if to chant my way/ into something worthy of your affection." At other times, the reaction is love: "if we fracture a system long enough/ our voices build/ a neoteric system/ with our voices inside." The voices in these poems are never truly singular. POC, trans/queer individuals and all marginalized people hold evolutionary revolutions in our cells. In language and elements, we are a collective. Survival held in our adaptation-another action that culls from us. We summon the magic inside of us to create a world in which we see ourselves beyond the death expected of us. We pray to our own tongues to conjure ourselves into existence. This book longs for a sanctuary of self-the dwelling of initial energy needed for our collective fight for human rights"--